ANALISIS PENGGUNAAN MODAL KERJA UNTUK MENINGKATKAN PROFITABILITAS DI CV AULIA PRIMA TEKNIK MAKASSAR - Lukman Lukman (Jurnal Bisnis dan Kewirausahaan, 2017)
This type of research is used aims to measure quantitative efficiency of use of working capital for the acquisition of profit in order to get a complete cost information, the analysis in use i.e. working capital needs analysis, analysis of working capital ratio and the ratio of profitability. aiming to evaluate the company's performance based on financial statements. The results of this study showed that the use of working capital not optimal due to working capital needs that decline and abundant stock.